ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2016) - Izzatin Nayli; Ronny Malavia Mardani (UNIVERSITAS ISLAM MALANG, 2018)
Abstract This reseach aims to determine the influence of Good Corporate Governance on Banking Firm Value listed Indonesian Stock Exchange in the year 2014-2016. The population in this research is Banking Company listed on Indonesian Stock Exchange in period 2014-2016 as many as 43 companies. The sample in this research purposive sampling method as many as 32 companies.Data analysis method used is Goodness Of Fit test to show the influence of independent variable to dependent variable, with classical assumption test. From the result of this study shows that the Board size (BS) and Board Of Independent Commissioners (INDP) not significant to Firm Value. But CEO Duality (CD) have a significant influence on Firm Value.Keywords: Board Size (BS), Board Of Independent Commissioners (INDP), CEO Duality (CD) and Firm Value.